A Sense of No Future in an Uncertain Present: Altruism and Risk-Seeking among Syrian Refugees in Jordan - Nora El-Bialy; Elisa Fraile Aranda; Andreas Nicklisch; Lamis Saleh; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2020)
An unprecedented number of refugees from Syria has sought refuge in both the Middle East and Europe since the beginning of the civil war in Syria in 2011. We analyze the level of altruism and risk-seeking among Syrian civil war victims in Jordan. We find systematic variations in their revealed levels of altruism and their willingness to accept risk: feeling as if having no future coincides with both more egoistic and more risk-seeking behavior. Refugees' behavioral responses and their sense of no future correlate with their current personal living experiences. Our findings suggest that both the sense of no future and the accompanying behavioral responses are primarily associated with miserable current living conditions rather than with experiences directly related to the civil war in Syria. Policy implications of these findings seem straightforward: Policy makers need to provide additional assistance for facilitating family reunion.
Keywords: C92; D64; D81; D91; F22; H56; Z13; 330; experiments; altruism; risk-seeking; psychological distress; migration; civil war